Проблеми впровадження та функціонування внутрішнього аудиту на авіаційних підприємствах в Україні - Остапенко, О. М.; Ostapenko, O. (КНТУ, 2015)
У статті узагальнено існуючу методику організації внутрішнього аудиту на підприємстві та запропоновано її вдосконалення відповідно до галузевих особливостей авіаційного транспорту. Доведено, що аудит впливає на фінансово-господарську діяльність авіаційних підприємств шляхом перевірки інформації, яка використовується при складанні звітності, попереджує виникнення помилок в обліку, сприяє раціональному використання ресурсів, покращує фінансову дисциплінарність матеріально-відповідальних осіб, попереджує та усуває зловживання, покращує фінансовий стан підприємства, прогнозує їхню подальшу діяльність. Today, a very important issue in Ukraine is the issue of the implementation and functioning of the internal audit of the aviation company as a system to ensure its effective functioning through assessment, analysis and control in enterprise management, management personnel, compliance with the established regime or policies of accounting as a result of verification of the financial statements.The paper summarizes the existing methodology of internal audit at the company and asked to improve it in accordance with the features of the air transport industry. In general, the organization of the internal audit department at the aviation enterprises can be recommended to carry out the following basic steps: preparation of a number of issues for which formed the internal audit department in the aviation enterprise; issuing administrative document on creation of the director of internal audit; formation of a system of posts and allocation of responsibilities between the employees of service; Integration of Internal Audit with other units of the management structure of the enterprise; the development of in-house internal audit standards regulating the activities of internal audit services to clearly define the rights and duties of service workers, to avoid confusion in the work, the timing of reporting information to management on the results of checks, forms of documentation and reports etc.
Problems of Implementation and Functioning of the Internal Audit at the Aviation Enterprises in Ukraine
Keywords: внутрішній аудит; власники; ризики бізнесу; прийняття рішень; внутрішній контроль; internal audit; owners; business risks; decision making; internal controls